Perancangan UI/UX Sistem Perusahaan Manajemen Properti Dengan Metode UX Design Thinking Pada CV Serene Bali - I Komang Bisma Bendesa Jaya; Ida Ayu Gde Suwiprabayanti Putra; Putu Praba Santika (Jurnal Pengabdian Informatika, 2026)
A good UI/UX design can enhance productivity and user satisfaction, as well as simplify workflows byminimizing errors and confusion. This journal aims to describe the process and results of designing UI/UXfor a property management system using the UX Design Thinking methodology. This methodology consistsof five main stages: empathize, define, ideate, prototype, and test. By implementing the UX Design Thinkingmethod, it is hoped that a system will be developed that improves efficiency and user comfort in propertymanagement. It is also hoped that this system will serve as a reference for the company to further develop thesystem. The results indicate that the UI/UX design has been successfully created and provides an overview ofhow the system will be implemented in the property management system.